Interprofessionality and mental health care: experiences of a PET-Health group in the Midwest region (Research, Society and Development, 2020)
Objective: To describe the experiences and repercussions of the actions of the thematic group on Mental Health of the Education through Work for Health Program (PET-Saúde) Interprofessionality at the Federal University of Mato Grosso for training and interprofessional work. Methodology: This is an account of the experiences of the Thematic Group on Mental Health at PET-Health Interprofessionality on teaching, research and extension actions carried out in the city of Cuiabá-MT. The actions were guided by the pedagogy of autonomy and carried out from the Arco de Maguerez and Tree of problematization in five stages: Observation of reality; Identification of key points; Theorization; Survey of solution hypotheses; and Application to reality. To strengthen the construction of the second stage of the Arch, the Problematization Tree was used. Results: The Problem Tree identified the lack of interprofessionality in training and service; and the disarticulation of the Psychosocial Care Network as the main demands. To this end, intervention-research was carried out with health professionals on interprofessionality, discussion on Psychiatric Reform with students, workshops and courses on the Network with the community and professionals, and activities to promote mental health to students, the community and professionals. Final considerations: Therefore, PET-Saúde presented itself as an instrument for the strengthening and integration of the teaching-service-community axes, and provided the development of interprofessional education, collaborative practices and mental health care.